The wise merchant - Baerle, Caspar van, 1584-1648 (Amsterdam University Press, 2019)
On 9 January 1632, at the inauguration of the Amsterdam Illustrious School - the predecessor of the city's university - Caspar Barlaeus delivered a speech that has continued to arouse the curiosity of researchers and the general public alike: 'Mercator sapiens'. This famous oration on the wise merchant is now considered a key text of the Dutch Golden Age. At the same time it is surrounded by misunderstandings regarding Barlaeus himself, the nascent Illustrious School, and Amsterdam's merchant culture.00This volume presents the first English translation and the first critical edition of the 'Mercator sapiens', preceded by an introduction providing historical context and a fresh interpretation of this intriguing text.